The effect of health education on quality of life (QOL) among polycystic ovary syndrome (PCOS) females at Karachi, Pakistan - Saleem, Madiha; Ali, Amjad; Hassan , Jahan Ara; Farooqui, Waqas Ahmed; Haroon, Rukhsana; Qasim, Rubina (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the effect of nurses-led health education intervention on quality of life among polycystic ovary syndrome females. Method: The quasi-experimental study was conducted from May to August 2022 at the Obstetrics and Gynaecology outpatient department of Dow University Hospital, Karachi, and comprised married females aged 18-45 years, who were diagnosed with polycystic ovary syndrome based on the Rotterdam criteria. Nurses-led health education intervention session was conducted for all the patients. Data was collected using the self-administered polycystic ovaries syndrome quality of life scale. Data was analysed using SPSS 26. Results: Of the 50 females, 26(52%) were aged 26-35 years. There was a significance difference between baseline and post-intervention scores across all domains of quality of life (p<0.05). Also, baseline body mass index of the participants was 30.4±4.711 which went down post-intervention to 29.4±4.800 (p<0.001). Conclusion: Nurses-led health education intervention improved the quality of life and body mass index of polycystic ovary syndrome patients. Key Words: Health education, Quality of life, Polycystic ovary syndrome.